Relationship of airway wall thickening to an imbalance between matrix metalloproteinase-9 and its inhibitor in asthma. Issue 4 (24th March 2005) - Matsumoto, H; Niimi, A; Takemura, M; Ueda, T; Minakuchi, M; Tabuena, R; Chin, K; Mio, T; Ito, Y; Muro, S; Hirai, T; Morita, S; et al.
Abstract : Background: The balance between matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of metalloproteinase-1 (TIMP-1) may be critical in extracellular matrix remodelling, a characteristic of asthmatic airways. An excess of TIMP-1 over MMP-9 has been associated with chronic airflow obstruction but the mechanisms underlying this association remain unknown. Recent computed tomographic (CT) studies indicate that airway wall thickening is associated with chronic airflow obstruction. Methods: Sputum levels of MMP-9, TIMP-1, and their molar ratio were examined in 26 patients with stable asthma and their relationship with pulmonary function and airway wall thickness, assessed by a validated CT technique which measured wall area corrected by body surface area (WA/BSA), the ratio of WA to outer wall area (WA%), and the absolute wall thickness corrected by √BSA of a segmental bronchus (T/√BSA), was examined. Results: Sputum MMP-9 levels were inversely correlated with WA% and TIMP-1 levels were positively correlated with WA/BSA and T/√BSA. The MMP-9/TIMP-1 molar ratio was inversely correlated with WA% and T/√BSA and positively correlated with post-bronchodilator values of mid-forced expiratory flow and maximum expiratory flow at the quartile of lung volume. Conclusion: Excess TIMP-1 may have a pathogenetic role in airway wall thickening in asthmatic patients which may result in chronic airflow obstruction.